Nickel cobaltite nanoparticles: preparation, characterization, and catalytic activity - Amini, Mojtaba; Ghameshloo, Fatemeh Bakhshi; Gautam, Sanjeev; Chae, Keun Hwa (SPRINGER HEIDELBERG, 2019)
The preparation and characterization of binary spinel nickel cobaltite, NiCo2O4 are presented by two methods. The prepared NiCo2O4 nanocomposites were tested for 1,3-dipolar cycloaddition reaction of different benzyl halides with phenylacetylene. The heterogeneity of the NiCo2O4 catalytic system was investigated using a hot filtration test, indicating that there is virtually no catalyst leaching into the reaction solution under the applied reaction conditions. Furthermore, our results show that the catalytic system can be reused four times without significant loss of stability or any additional treatment.
Keywords: FACILE SYNTHESIS; CLICK REACTION; COPPER; CYCLOADDITION; COMBUSTION; AZIDES